Phosphorus Availability Affecting the Diversity of Arbuscular Mycorrhizal Fungi (AMF) in the Artisanal Gold Mining Area - Jayani, Faradila Mei; Faridah, Eny; Nurjanto, Handojo Hadi; Riniarti, Melya (Jurnal Manajemen Hutan Tropika, 2024)
Arbuscular mycorrhizal fungi (AMF) diversity is influenced by biotic and abiotic factors. Several studies have shown the presence of AMF in ex-gold mining areas with low soil fertility and heavy metal accumulation. The purpose of this study was to analyze the diversity of AMF species in artisanal gold mining areas. The experimental design used is randomized group design with two treatment factors: the interval distance range from tailings disposal point (A) and the vegetation type (B). Interval distance treatment consisted of two levels (A1: 0-10 m and A2: 10-20 m). Vegetation type treatment (B) consists of three levels (B1: Theobroma cacao, B2: Mangifera indica, B3: Artocarpus heterophyllus). Some types of AMF spores found are Acaulospora sp. 1, Acaulospora sp. 2, Acaulospora sp. 3, Acaulospora sp. 4, and Acaulospora sp. 5. The index of species richness and diversity of AMF species in the artisanal gold mining area is low. The existence of AMF symbiosis with plants in artisanal gold mining areas is also indicated by the presence of colonization in the roots of T. cacao, M. indica, and A. heterophyllus with a low to medium category. Pearson correlation test results showed that AMF species diversity index and P availability were not correlated (r = -0.204, p-value = 0.699). Pearson correlation test results also show that AMF colonization and P availability are not correlated (r = -0.756, p-value = 0.082). Although not correlated, based on the graph, it can be seen that the higher the available P element, the smaller the index value of species diversity and AMF colonization.